Mutual Insurance, Economic Democracy, and Legal Certainty: An Indonesian Constitutional Perspective - Handayani, Wiwik; Jainah, Zainab Ompu; Rusli, Tami; Pasamai, Syamsuddin (As-Siyasi: Journal of Constitutional Law, 2026)
This article examines the constitutional position of mutual insurance as a manifestation of economic democracy within Indonesia's national insurance system. Following the Constitutional Court Decision Number 32/PUU-XVIII/2020, which declared Article 6 paragraph (1) of Law Number 40 of 2014 on Insurance conditionally unconstitutional, scholarly discussions have primarily focused on institutional and regulatory aspects of mutual insurance, while its constitutional significance as an embodiment of economic democracy and its implications for Indonesia's economic constitutionalism remain insufficiently explored. Employing normative legal research through statutory, conceptual, and historical approaches, this study uses Hans Kelsen's Pure Theory of Law to examine the normative consistency between constitutional principles and insurance legislation. In contrast, Gustav Radbruch's theory of legal certainty serves as the analytical framework for assessing the legal consequences of the existing regulatory vacuum. The analysis demonstrates that mutual insurance reflects the constitutional principles of collective ownership, participation, and kinship embodied in Article 33 paragraph (1) of the 1945 Constitution. Furthermore, the Constitutional Court Decision Number 32/PUU-XVIII/2020 establishes a constitutional obligation for the legislature to provide a statutory framework that recognizes the distinctive institutional character of mutual insurance, thereby transforming legal recognition from a regulatory policy into a constitutional mandate. Accordingly, this article contributes to the development of Indonesia's economic constitutionalism by reconceptualizing mutual insurance as a constitutionally protected economic institution whose sustainability depends upon legal certainty through comprehensive legislative reform.